Inward Turn of Narrative. - Kahler, Erich, 1885-1970 (Bollingen Series (General), 2017)
Erich Kahler sees cultural history as a subtle process in which reality plays upon consciousness and consciousness itself is forever transforming reality. He traces the ebb and flow of this relationship by studying changes in narrative form from its beginnings in the Gilgamesh Cycle to the end of the eighteenth century. The general direction is toward a growing inwardness, he finds; what takes place is an expansion of consciousness as man constantly draws outer space, the contents of a more and more complex world, into what Rilke called Weltinnenraum, "inner space."Originally published in 1973. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905